Use of the self as a therapeutic tool: a formative experience of occupational therapy in an undergraduate course - León, Joselyn Valenzuela (2022)
Introduction:The use of the self as a therapeutic tool is a client-centered practice with the least evidence in the pedagogy of occupational therapy. In Chile, experiential subjects arise, linked to artistic/playful methods that seek to influence the skills of the undergraduate student for their development. Objective:To analyze the experience of the students in relation to the learning, characteristics, and contributions of the subjects that contribute to the development of the use of the self as a therapeutic tool, in occupational therapy careers at universities in the south of Chile. Method: Qualitative research, exploratory with a grounded theory design. The sampling was non-probabilistic, intentional, by criteria, of fifteen students in the professional internship stage. Data collection was through two focus groups, after signing informed consent. The analysis was carried out using the constant comparison method of Glaser and Strauss, using the Atlas Ti program to systematize the information. Scientific rigor was guarded by the criteria of Guba and Lincoln. Results: 530 units of meaning are identified, 30 descriptive open codes, grouped into eight axial categories, emerging two thematic nuclei that address the “Teaching-learning process in the formation of the Use of the Self” and the “Professional Development for the Use of the Self”. Conclusion: For the students, the methodologies used to contribute in a relevant way to the development of self-knowledge and key generic competences for the “Use of the Self”. This pedagogy could be complemented with other active strategies to ensure the centrality of the user in occupational therapy.